Popularisation of medical knowledge in online forums - Boginskaya, Olga (Slavia Centralis, 2022)
The article investigates Russian popular medical science discourse which has barely been studied in terms of popularisation strategies used in expertlay interaction where a set of specialised concepts needs to be displayed in a way that enables a lay audience to understand them. The study was, thus, motivated by the lack of guidance for interacting with non-expert lay Internet users, and challenges faced by them in attempting to understand unfamiliar medical concepts. The findings support the study’s central argument that experts use a different rhetoric to communicate with a lay audience than they use with their peers, and the explanatory strategies help them to overcome the incomprehensibility of expert discourse, indicating that efforts should be undertaken to explain specialised concepts to non-experts.
Keywords: pojasnjevalna strategija; asimetrija znanja; medicinski diskurz; populariziran diskurz